Vortical flows - Wu, J.-Z. (Jie-Zhi); Ma, H.-Y. (Hui-Yang).; Zhou, M.-D. (Ming-De).; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2015)
This book is a comprehensive and intensive book for graduate students in fluid dynamics as well as scientists, engineers and applied mathematicians. Offering a systematic introduction to the physical theory of vortical flows at graduate level, it considers the theory of vortical flows as a branch of fluid dynamics focusing on shearing process in fluid motion, measured by vorticity. It studies vortical flows according to their natural evolution stages, from being generated to dissipated. As preparation, the first three chapters of the book provide background knowledge for entering vortical flow.
Electronic reproduction.
Keywords: Vortex-motion.; Electronic books